Auditor Terms and Term Limits in the Public Sector: Evidence from the US States - Mark Schelker (Center for Research in Economics, Management and the Arts (CREMA), 2009)
Improving transparency and enabling the principal to hold its agents accountable is a major issue in any principal agent relationship. This paper focuses on the role of public auditors in this task and presents evidence on the impact of auditor term length and term limits on government performance at the US State level. While the empirical results for the influence of term length are ambiguous, I find strong evidence for a positive and significant influence of term limits on state credit ratings. Auditors who face a binding term limit seem to be more effective monitors, which improves credit ratings.
Keywords: H11; H83; D70; H10; 330; Direct Democracy; public auditor; tenure length; term limit; governance